Sistem Informasi Stok Gudang Koperasi Menggunakan Supply Chain Management - Khusna, Arfiani Nur; Nugraha, Fahmi Ardhi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2018)
The cooperative is faced with the problem of how to keep the availability of goods in the warehouse sufficient, not experiencing upperstock or understock in the stock inventory system. The Supply Chain Management approach can help overcome the problem of availability of goods by integrating suppliers efficiently. The study aims to produce information about the stock of goods and the number of orders for the next period so that it can make a suitable budget plan. Collecting data is the first step and then designing the pattern of supply chain management flow, supply chain management strategies include the use of pareto ABC classification to give priority to supervision of inventory and determination of purchase points by calculating Economy Order Quantity (EOQ), process flow, implementation and testing. The system produces goods stock information that is able to provide accurate information about the remaining stock of goods in the warehouse along with calculation calculations for the purchase of each item at an economical price and amount, for the determination of product reorder time (Reorder Point), the average product lead time is 2 days, the usage rate per day for rice is 0.34 and the safety stock of rice is 20 sacks so that if the rice has reached the 3 point sack then the cooperative must re-order. The test results using usability test showed that 66.66% of the questions were able to be answered by the respondents and the test results between 65-84% were declared good so that the application was feasible and usable.